Problematika Mekanisme Naturalisasi Istimewa terhadap Prinsip Transparansi Publik Di Indonesia - Alya Azrah Fahmi Achmad; Mahendra Putra Kurnia; Insan Tajali Nur (Universitas Medan Area, 2026)
This article examines the mechanism of special naturalization from the perspective of public transparency within Indonesian citizenship law and proposes an ideal regulatory framework. Article 20 of Law Number 12 of 2006 authorizes the President to grant Indonesian citizenship to foreign nationals who have rendered outstanding services to the state. However, the provision lacks clear criteria, creating legal ambiguity and broad discretionary interpretation. This study employs normative legal research using statutory and conceptual approaches. The findings indicate that the current mechanism affects public transparency, legal certainty, equality before the law, and the principle of limitation of power due to the lack of transparency in the decision-making process. The novelty of this research lies in analyzing special naturalization through the perspective of public transparency in relation to the principle of limitation of power. The study recommends revising Article 20 by establishing clear criteria, transparent procedures, public information disclosure, and effective oversight mechanisms to ensure transparency, accountability, and legal certainty in the implementation of special naturalization.